Adult Human and Mouse Ovaries Lack DDX4-Expressing Functional Oogonial Stem Cells. Issue 1 (January 2016) - Zhang, Hua; Panula, Sarita; Petropoulos, Sophie; Edsgärd, Daniel; Busayavalasa, Kiran; Liu, Lian; Li, Xin; Risal, Sanjiv; Shen, Yan; Shao, Jingchen; Liu, Meng; Li, Susann; et al.
Abstract : Obstet Gynecol Surv 2016;71(1):29–30 The generally accepted viewpoint for more than 50 years has been that the number of oocytes is fixed in fetal or neonatal ovaries, and therefore, oocytes cannot renew themselves in postnatal or adult life. Over the past decade, however, the traditional viewpoint has been challenged by a number of investigators who have presented evidence that postnatal follicular renewal occurs in mammals, and that mitotically active oogonial stem cells (OSCs) exist in postnatal mouse ovaries.